Graphene Oxide Reduction Recipes, Spectroscopy, and Applications - Gao, Wei (Springer, 2015)
Abstract This chapter introduces a peculiar organic macromolecule previously named as graphitic acid, graphite oxide (GO), or more recently, graphene oxide (GO). It is basi cally a wrinkled two-dimensional carbon sheet with various oxygenated functional groups on its basal planes and peripheries, with the thickness around 1 nm and lateral dimensions varying between a few nanometers to several microns. It was first prepared by the British chemist B. C. Brodie in 1859 and became very popular in the scientific community during the last decade, simply because it was believed to be an important precursor to graphene (a single atomic layer of graphite, the discovery of which won Andre Geim and Konstantin Novoselov the 2010 Nobel Prize in Physics). Several strate gies have been introduced to reduce GO back to graphene; however, in this chapter we will mainly focus on GO itself and, more relevantly, its synthesis, chemical structure, and general characterizations. We emphasize here that, despite its strong relevance to graphene, GO also has its own scientific significance as a basic form of oxidized carbon and technological importance as a platform for all kinds of derivatives and composites that have already demonstrated various interesting applications...